2017
DOI: 10.1590/1807-1929/agriambi.v21n9p640-644
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical composition of native fruits of the Ceará coast at different development stages

Abstract: A B S T R A C TThis study aimed to evaluate the physico-chemical composition of native fruits of the Ceará coast at different development stages. The fruits of 'guajiru' , 'manipuçá' , 'murici-pitanga' and 'murta' were collected during the year 2014, and the following evaluations were made: total soluble solids, total titratable acidity, pH, total soluble solids and titratable acidity ratio. A completely randomized design was used, with 5 or 6 treatments, depending on the maturation stage and 4 replicates. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Eugenia punicifolia (Kunth) DC. (Myrtaceae), popularly known as myrtle, is a plant commonly found in the coast of Ceará (BRAZ et al, 2004;BFG, 2015;GONÇALVES et al, 2017). It has fruits very appreciated by wild animals and its leaves have compounds with antioxidant, antinoceptive and anti-inflammatory effect (GALENO et al, 2014;BASTING et al, 2014;PEDRONE, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Eugenia punicifolia (Kunth) DC. (Myrtaceae), popularly known as myrtle, is a plant commonly found in the coast of Ceará (BRAZ et al, 2004;BFG, 2015;GONÇALVES et al, 2017). It has fruits very appreciated by wild animals and its leaves have compounds with antioxidant, antinoceptive and anti-inflammatory effect (GALENO et al, 2014;BASTING et al, 2014;PEDRONE, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the composition of phenolics is quite variable, depending on the type of fruit and the environmental conditions to which they are subjected (Lado et al, 2018). The phenolic content of capoeira-branca fruit is low when compared to some fruits, such as strawberry (Gonçalves et al, 2017), buriti (Rudke et al, 2019) and blueberry (Zhang et al, 2016), since these fruits are rich sources of these compounds. However, capoeira-branca fruit presented phenolic compounds content close to wild cherry plum (Smanalieva et al, 2019).…”
Section: Vitamin C and Phenolic Contentmentioning
confidence: 99%
“…Currently, several studies have evaluated the influence of different maturation stages on unconventional fruit characteristics, that is, those of little economic relevance and which are usually not part of human food, such as blueberry (Pérez & Mojica, 2018), besides several Brazilian native fruits (Gonçalves et al, 2017;Guedes et al, 2017;Henrique et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The harvest of fully ripe fruits provided an average increase of 1.55 ºBrix (29.9%), and should therefore be Storage for 48 hours caused an increase in titratable acidity (TA) of fruits harvested at E1; however, for fruits harvested at E2 and E3, the opposite was observed (Table 4). Evaluating different fruits native to the state of Ceará, Gonçalves et al (2017) observed that acidity had different behavior during ripening, not being possible to establish a single harvest pattern. For grumixama, Aguiar et al (2016) observed TA of 0.29% citric acid, close to value observed in this study.…”
Section: Grumixama (Eugenia Brasiliensis Lam)mentioning
confidence: 99%